A SOFTWARE COMPLEX FOR THE NUMERICAL SIMULATION OF GENERATION AND PROPAGATION OF TSUNAMI WAVES IN VARIOUS MARINE AREAS FROM DYNAMIC SEISMIC SOURCES - Kataeva L.Yu.; Romanov A.V.; Mazova R.Kh.; Kozhevnikov I.V. (My University, 2006)
A software complex is designed for the simulation of tsunami generation by a dynamic seismic source consisting of several vertically moving blocks of a preset configuration. The program interface allows the user to change the source kinematics of the blocks as a function of the seismic source under consideration. The software makes it possible to display the tsunami wave propagation in a water area (unconstrained by concrete conditions), perform its monitoring, interrupt and resume computations, depict the tsunami wave propagation front, display the distribution of maximum wave heights in a marine area, construct histograms of maximum wave heights along a coastline, and construct the velocity fields of particles in the traveling wave, wave front velocities, and mareograms at any given points of the area under consideration. Using the software capabilities, current data and their variation in time can be obtained at any point of the calculation domain, and all results (both final and intermediate) can be saved in the form of both numerical data and plots or diagrams.
Keywords: PROGRAM INTERFACE; MATHEMATICAL MODEL; SHALLOW WATER EQUATIONS; SOFTWARE PRODUCT